A man for all seasons: Woodrow Wilson, transatlantic relations and the war against militarism. (2nd October 2018) - Cox, Ashley
Abstract : This paper investigates the role of transatlantic Wilsonian values in the entry of the United States in to the First World War. Arguing that the offshore balancing thesis and economic rational are not sufficient to explain US entry and we must engage with Wilsonian explanations to understand this conflict.